Effective Communication in Building Relationships Between Parents and Children - Nur Hasanah Harahap; Dinny Rahmayanty; Asmawati ‍‍; Angga Widyansyah Pratama; Rahmi Syarima Afdhol (Universitas Muhammadiyah Enrekang, 2023)
Effective communication between parents and children plays an important role in the establishment of healthy and close relationships within the family. This article examines the importance of open communication and understanding in overcoming the various challenges parents face in raising children. We highlight communication strategies that can help parents build strong emotional connections with their children, including methods of attentive listening, responding positively, and overcoming common communication barriers. By understanding and applying these principles of effective communication, parents can create a supportive environment for their children's development and foster harmonious family relationships.